A longitudinal evaluation of cardiovascular risk factors, treatment patterns, and outcomes in patients with documented cardiovascular disease treated with lipid lowering therapy in the United Kingdom. (25th November 2020) - Beaini, Y; Danese, M; Sidelnikov, E; Villa, G; Catterick, D; Iqbal, M; Gleeson, M; Lubeck, D; Patel, J
Abstract: Background: Over time, guidelines for dyslipidemia management in patients at high risk of atherosclerotic cardiovascular disease (CVD) changed with the goal of improving patient outcomes. Guidelines have been released by the European Joint Task Force in 2007, 2012 and 2016, European Society of Cardiology in 2011, 2016 and 2019, Joint British Societies in 2014, and National Institute for Health and Care Excellence in 2014. Purpose: Evaluate cardiovascular risk factors, treatment patterns, and cardiovascular outcomes over time related to dyslipidemia management. Methods: Ten prevalent cohorts of patients with documented CVD receiving lipid-lowering therapy (LLT) were created using Clinical Research Practice Datalink (CPRD) records as of January 1, each year from 2008 through 2017. For each cohort, we identified CVD risk factors and LLT, and estimated the 1-year composite rate of fatal and nonfatal myocardial infarction (MI), ischemic stroke (IS), or revascularization. Patient follow-up was censored at the earliest of one year, end of data, or the outcome of interest. Patients in each cohort were required to be ≥18 years old, have ≥1 years of available medical history, and have received ≥2 LLT prescriptions in the prior year. Documented CVD was defined as MI, IS, angina, revascularization, transient ischemic attack, carotid stenosis, abdominal aortic aneurysm, or peripheral arterial disease. Patients could be in multiple cohorts. Results: Annual patient counts ranged from 170, 501 to 179, 137 through 2013 and declined to 94, 418 by 2017 (due to fewer patients in the overall CPRD data). Comparing 2008, 2011 (when ESC guidelines were revised) and 2017 showed the following for CVD risk factors: mean age was 71.6, 72.3, and 72.5 years; males were 59.9%, 61.1%, and 63.1%; current smoking was 15.1%, 15.2%, and 13.9%; type 2 diabetes was 18.4%, 20.2%, and 22.4%; stage 3–5 chronic kidney disease was 22.4%, 25.1%, and 22.8%; history of MI was 22.5%, 23.9%, and 27.4%; history of IS was 5.5%, 6.6%, and 7.9%; LDL <1.8 mmol/L was 27.8%, 29.2% and 37.2%; and LDL <1.4 mmol/L was 9.9%, 10.1%, and 15.6%. In terms of treatment, high intensity statin use increased from 12.9% to 15.7% to 30.8%; atorvastatin 40–80 mg use increased from 12.9% to 15.5% to 30.5%; while simvastatin 20–40 mg use decreased from 55.4% to 58.8% to 36.7%. The 1-year cardiovascular event rate declined from 2.54 to 2.35 to 1.96 events per 100 person-years (Figure). Conclusions: After 2011 in the UK, there was an increased use of high intensity statins, a greater proportion of patients with LDL levels <1.8 and <1.4 mmol/L, and lower 1-year cardiovascular event rates. While improved CVD management likely contributed to the event rate decline, less than 40% of very high-risk patients achieved an LDL <1.8 mmol/L, and the proportion with LDL <1.4 mmol/L, as recommended by the 2019 ESC guidelines, was less than 20%. Clinicians should continue their efforts to reduce LDL in these patients. Funding Acknowledgement: Type of funding source: Private company. Main funding source(s): Amgen